Performance of microwave incinarated rice husk ash and used engine oil as a green concrete admixtures - Salmia B.; Nuruddin M.F.; Shafiq N.; Nur Liyana M.K.; Talib S.H.A. (Taylor's University, 2023)
The utilization of waste materials in the construction industry is a novel approach let alone if these materials can further enhance the durability of the structures. Amongst the waste materials identified to be incorporated in this study is Rice Husk Ash (RHA) and Used Engine Oil (UEO). Productions of these waste materials are colossal with annual volume of 1.35 billion gallon and 40 million tons of used engine oil and rice husk respectively. The main aim of this research is to establish the effects of these two waste materials (as ingredients) in concrete. The rice husk was burn using microwave incinerator to produce better quality of Microwave Incinerated Rice Husk Ash (MIRHA). The pozzolanic reactivity of MIRHA helped to enhance concrete durability. The used engine oil acted as an admixture that improved the fresh state of the concrete. Workability, entrained air and compressive strength tests were conducted and the result showed that the concrete illustrated better performance compared to control sample in terms of workability, air contain and compressive strength. School of Engineering, Taylors University.